ธรณีวิทยาโครงสร้างของหินปูนยุคเพอร์เมียน บริเวณเขาถ้ำงูเหลือม อำเภอปากช่อง จังหวัดนครราชสีมา - ธนพ ศิริวัฒนานุรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Limestone in Saraburi-Pak Chong, Nakhon Ratchasima is an important law material for construction factory of Thailand. This area is a part of Khao Khwang Platform which have been deformed since the collision between Sibumasu Plate and Indochina Plate during Early Triassic. This study focuses on structural geology of the Permian limestone at Khao Tham Ngulueam in order to construct an evolutionary model presenting deformation history of Khao Khwang Platform. According to field study, two types of limestone have been classified base on their thickness; (1) thick limestone and (2) thin limestone interbeded with shale. Fault propagation fold found in the study area indicates tectonic transportation from southeast to northwest. In addition, there is a lot of fault that moved both vertical and horizontal by tectonic force which related to Indosinian Orogeny from Early Triassic to Late Triassic. Moreover, variation of fracture orientation suggests difference force direction. Fusulinid, Brachiopod, Coral and Algae indicate shallow marine environment.